Pengaruh E-Commerce, Pengetahuan Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa (Studi Pada Mahasiswa Program S1 Manajemen Sekolah Tinggi Ilmu Ekonomi Riau Pekanbaru) - Elida Gultom (Forum Kerjasama Pendidikan Tinggi, 2021)
This research was conducted with the aim of seeing and knowing whether the influence of e-commerce, entrepreneurial knowledge and family environment on the entrepreneurial interest of students in the S1 Management School of Economics College (STIE) Riau. This study uses primary data obtained from the results of filling out questionnaires by respondents with purposive sampling data collection techniques. The population is all students majoring in S1 Management with a sample of 100 respondents with the criteria that they have followed the entrepreneurship course. This research method uses descriptive research with a quantitative approach. The data analysis technique used is Multiple Linear Regression with the help of SPSS. The conclusion of this study is that simultaneously e-commerce, entrepreneurial knowledge and family environment have a significant effect on interest in entrepreneurship. Partially, E-commerce and family environment have no significant effect on interest in entrepreneurship, while entrepreneurial knowledge has a significant effect on interest in entrepreneurship. The magnitude of the influence of e-commerce, entrepreneurial knowledge and family environment on the entrepreneurial interest of students of the STIE Riau S1 Management Program is 56.2%. As for the variable that most influences the interest in entrepreneurship of students in the S1 Management program, STIE Riau, is entrepreneurial knowledge.